Combustion Synthesized Zinc Oxide Electron‐Transport Layers for Efficient and Stable Perovskite Solar Cells. (25th February 2019) - Zheng, Ding; Wang, Gang; Huang, Wei; Wang, Binghao; Ke, Weijun; Logsdon, Jenna Leigh; Wang, Hanyu; Wang, Zhi; Zhu, Weigang; Yu, Junsheng; Wasielewski, Michael R.; Kanatzidis, Mercouri G.; et al.
Abstract: Perovskite solar cells (PSCs) have advanced rapidly with power conversion efficiencies (PCEs) now exceeding 22%. Due to the long diffusion lengths of charge carriers in the photoactive layer, a PSC device architecture comprising an electron‐ transporting layer (ETL) is essential to optimize charge flow and collection for maximum performance. Here, a novel approach is reported to low temperature, solution‐processed ZnO ETLs for PSCs using combustion synthesis. Due to the intrinsic passivation effects, high crystallinity, matched energy levels, ideal surface topography, and good chemical compatibility with the perovskite layer, this combustion‐derived ZnO enables PCEs approaching 17–20% for three types of perovskite materials systems with no need for ETL doping or surface functionalization. Abstract : An effective approach to low temperature, solution‐processed ZnO electron‐transport layers (ETLs) for perovskite solar cells by combustion synthesis is developed. Due to the intrinsic passivation effects, high crystallinity, matched energy levels, ideal surface topography, and good chemical compatibility with the perovskite layer, combustion‐processed ZnO electron transport layers enable power conversion efficiencies approaching 17–20% for three representative perovskite systems without ETL doping or surface functionalization.